2016
DOI: 10.1186/s40249-016-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

A community-based prospective cohort study of dengue viral infection in Malaysia: the study protocol

Abstract: BackgroundGlobally, dengue infections constitute a significant public health burden. In recent decades, Malaysia has become a dengue hyper-endemic country with the co-circulation of the four dengue virus serotypes. The cyclical dominance of sub-types contributes to a pattern of major outbreaks. The consequences can be observed in the rising incidence of reported dengue cases and dengue related deaths. Understanding the complex interaction of the dengue virus, its human hosts and the mosquito vectors at the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Participants were recruited from three localities (villages) within the Sungai Segamat subdistrict representing rural, urban, and semi-urban communities. Based on notified dengue cases, the three study localities had been identified as the dengue epicenter in the Sungai Segamat subdistrict since 2009 [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants were recruited from three localities (villages) within the Sungai Segamat subdistrict representing rural, urban, and semi-urban communities. Based on notified dengue cases, the three study localities had been identified as the dengue epicenter in the Sungai Segamat subdistrict since 2009 [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The comprehensive study protocol has previously been described by Jahan et al [ 11 ], and is briefly described here. Essentially, this study extended slightly over a one-year period and consisted of four phases of data and blood collection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, dengue infections constitute a significant public health burden. Nearly two‐thirds of the global population is at risk, mainly in African, Asian and American inter‐tropical developing countries. In the last half century, the prevalence of the dengue virus (DENV) has increased dramatically (up to 30%) worldwide, especially in Sub‐Saharan Africa .…”
mentioning
confidence: 99%